Stepped impedance interdigital capacitive RF sensor for continous blood glucose monitoring - Muhammad Farhan Affendi Mohamad Yunos (Kulliyyah of Engineering,International Islamic University Malaysia, 2021)
Diabetes is a growing chronic disease that affects millions of people in the world. Regular monitoring of blood glucose levels in patients is necessary to keep the disease under control. Current methods of blood glucose monitoring devices are typically invasive, finger pricking to extract blood, causing discomfort to the patients. Non-invasive glucose monitoring is a possible game-changer for diabetic patients as it reduces discomfort and provides continuous monitoring. Interdigital sensors have been implemented in various applications such as chemical and biological sensing and have shown good sensitivities. This work describes the design and fabrication of an interdigital sensor (IDT) that has the potential of estimating blood glucose levels using capacitive measurements. The interdigital sensor produces an electric field that penetrates the material under test and detects the changes in the dielectric constant of the material. When used on top of the skin, it can be used to detect permittivity changes in the skin and the blood vessels underneath it. The IDT sensor was first designed using theoretical equations and later was optimized by using CST Microwave Studio®. Upon completion of simulations, the sensor was fabricated using copper-clad FR4 boards. The fabricated sensors were measured using an RF analyzer. This stepped impedance component was added to the sensor so that it has low noise and high Q-factor. In addition, a microfluidic device structure that imitates the real vessel structure on the human hand was fabricated to measure the change in permittivity for different glucose concentrations. During experiments, the IDT sensor was tested with varying glucose concentrations (0 to 240 mg/dL). The S11 frequency response was measured and the relationship between S11 resonant frequency and glucose concentration was plotted. It was observed that as the glucose concentration increases, the frequency values also increases. The linear relationship between frequency and glucose concentration was also plotted the sensitivity (slope) and the limit of detection (LOD) of the sensor. The result shows that the sensitivity of the biosensor is 264.2 kHz/mgdL-1, and LOD was calculated to be at 29.89 mg/dL. This indicates that the IDT sensor has good potential to be a non-invasive sensor for glucose monitoring.